Alpha-1-Antitrypsin Deficiency in Children: Case Series - Svetlana I. Melnik; Nikolay N. Vlasov; Marina V. Pinevskaya; Elena A. Orlova; Svetlana V. Starevskaya; Irina Y. Melnikova (Вопросы современной педиатрии)
Alpha-1-antitrypsin deficiency (A1AT) is a cause of an orphan disease, cases of which are well described in adult patients, but as for children, they are described only in a few publications, and in most of them the description is limited to liver lesions. This article presents the results from the observation of 5 children with alpha-1-antitrypsin deficiency, including 3 boys (Z-allele homozygotes) and 2 girls (PiMZ-phenotype carriers). It is shown that in patients with A1AT deficiency the onset of the destruction of lung tissue was at the age of 2 with the signs of recurrent bronchial obstruction and at the age of 7 in the form of emphysema. Raising awareness among practicing physicians of various specialties will improve diagnostics of this form of disease and its comorbid conditions.